Pengaruh Cermin terhadap Peningkatan Motivasi dan Perilaku Kebersihan Gigi Anak di TK Arimbi Palembang - Arlianti, Silpi; Rhomawati, Yuli; Adinda, Nadila Betha; Marlindayanti, Marlindayanti; Wijaya, Dhandi (Jurusan Kesehatan Gigi, Poltekkes Kemenkes Palembang, 2024)
Dental and oral health is important for general health and quality of life. Dental health is important, especially for children's development. Dental caries is a disorder that causes teeth to become porous due to food residue that sticks and causes calcification of the teeth. Mirrors are a health medium that can be used to increase motivation and change dental health behavior. This research aims to determine the effectiveness of using mirrors in increasing children's motivation and dental hygiene behavior at Arimbi Kindergarten, Palembang. The design of this research was experimental by conducting experiments aimed at finding out the effect of mirrors on increasing children's motivation and dental hygiene behavior. The sample using a purposive sample technique was obtained as many as 82 children. The group of children was asked 10 questions. Statistical analysis uses the T Test. The results showed that there was an influence of motivation with a value of P=0.001 (P<0.05) with an average motivation score of 1.26829 and children's dental hygiene behavior with a value of P-0.001 (P<0.05) with an average behavior score of 2.17073 . This shows that mirrors have an influence on increasing children's motivation and dental hygiene behavior.